แบบจำลองการตัดสินใจสำหรับระบบซื้อ-ขายความจุรถบรรทุก - มานพ เรี่ยวเดชะ (จุฬาลงกรณ์มหาวิทยาลัย, 2014)
The objective of this research is to develop Decision Model for Truck Capacity Trading System for garment industry. The research methodology consists of reviewed the Truck Capacity Trading System together with the involved theories and researches, design and developing of the decision model, including logic testing of the decision model. The yields of this research are the embed decision model for Truck Capacity Trading System in Left Over Truck Capacities Purchasing, Transportation Service Pricing , Truck Dispatching with system manual. The results of the research project were justified in the following aspects: accuracy and completeness of the system. The developed operation supporting system can be implemented in the real transportation environment and it is considered to be aptly responsive to the usability of all involving associates in Decision Model for Truck Capacity Trading System for garment industry. The evaluation of the developed system leads to satisfactory result. The developed system can be implemented in goods transportation among facilities of the garment industry. It can efficiently officers in truck trading capacity activity.